(untitled) (ENTHYMEMA, 2020)
This paper aims to identify the rhetorical strategies and the metaphors used within the representation of virtual reality beyond the field of digital poetry, through a screening of contemporary Italian poetry. Starting with a preliminary investigation on the metaphorical conversion of electronic devices into disturbing pets, the paper collects examples of water-surfaces as similes frequently adopted for the screen. The interaction with the Web 2.0 has been interpreted as a virtual capsule experience, where the subjects find themselves isolated and framed in a disintegrated relation with their surroundings. Hence I try to verify the consequences of such experience, speculating that poetical writing has been translating those characteristics into a redefinition of the stanza (as a textual capsule), the abundance of the figures of speech and the displaying of reversible textual sequences.